2022
DOI: 10.1038/s41380-022-01656-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutamate-carboxypeptidase-II in dorsolateral prefrontal cortex: potential therapeutic target for neuroinflammatory cognitive disorders

Abstract: Glutamate carboxypeptidase-II (GCPII) expression in brain is increased by inflammation, e.g. by COVID19 infection, where it reduces NAAG stimulation of metabotropic glutamate receptor type 3 (mGluR3). GCPII-mGluR3 signaling is increasingly linked to higher cognition, as genetic alterations that weaken mGluR3 or increase GCPII signaling are associated with impaired cognition in humans. Recent evidence from macaque dorsolateral prefrontal cortex (dlPFC) shows that mGluR3 are expressed on dendritic spines, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…These receptors are localized on layer III spines, and they inhibit cAMPcalcium opening of K + channels, strengthening network connectivity and enhancing the dlPFC neuronal firing needed for higher cognition. mGluR3 are primarily post-synaptic in the primate dlPFC, and are not only stimulated by glutamate, but by N-acetylaspartylglutamate (NAAG), which is co-released with glutamate and is selective for mGluR3 [85,86]. α2A-ARs are often pre-synaptic receptors, but also play a major post-synaptic role in primate dlPFC where they are concentrated on dendritic spines near HCN channels [71].…”
Section: Pfc Circuits Have Unique Neuromodulation That Magnifies Toxi...mentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors are localized on layer III spines, and they inhibit cAMPcalcium opening of K + channels, strengthening network connectivity and enhancing the dlPFC neuronal firing needed for higher cognition. mGluR3 are primarily post-synaptic in the primate dlPFC, and are not only stimulated by glutamate, but by N-acetylaspartylglutamate (NAAG), which is co-released with glutamate and is selective for mGluR3 [85,86]. α2A-ARs are often pre-synaptic receptors, but also play a major post-synaptic role in primate dlPFC where they are concentrated on dendritic spines near HCN channels [71].…”
Section: Pfc Circuits Have Unique Neuromodulation That Magnifies Toxi...mentioning
confidence: 99%
“…GCPII is synthesized and released by glia, including large increases in GCPII expression by reactive microglia under conditions of inflammation [91,92]. Physiological studies in aged monkeys show that GCPII markedly lowers the dlPFC neuronal firing needed for higher cognition [86]. PDE4s are also lost with age in primate dlPFC [88,93], and this may involve MK2 inflammatory signaling unanchoring PDE4 from DISC1 [94].…”
Section: Pfc Circuits Have Unique Neuromodulation That Magnifies Toxi...mentioning
confidence: 99%
“…As mentioned above, GCPII degrades the neurotransmitter NAAG. After NAAG is released from presynaptic terminals, its cleavage by GCPII (which is expressed by both neurons and astrocytes [Yang et al, 2022]) produces glutamate and N‐acetyl aspartate. Therefore, inhibition of GCPII activity reduces local glutamate production.…”
Section: Proteolytic Cleavage Of Aβmentioning
confidence: 99%
“…Glutamate carboxypeptidase II (GCPII), also known as prostate-specific membrane antigen (PSMA), is a type II transmembrane metallopeptidase encoded by the folate hydrolase (FOLH1) gene in humans [ 1 ]. Since its discovery in 1987 [ 2 ], its expression in different tissues such as the prostate, kidney [ 3 ], small intestine [ 4 , 5 ], and central and peripheral nervous system [ 6 , 7 , 8 ] has been reported. In the brain, GCPII catalyzes the hydrolysis of the neurotransmitter N -acetylaspartylglutamate (NAAG) to N -acetylaspartate (NAA) and glutamate [ 9 ], and multiple independent research groups have demonstrated the therapeutic benefit of inhibiting GCPII to treat neurological dysfunctions [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in 1987 [ 2 ], its expression in different tissues such as the prostate, kidney [ 3 ], small intestine [ 4 , 5 ], and central and peripheral nervous system [ 6 , 7 , 8 ] has been reported. In the brain, GCPII catalyzes the hydrolysis of the neurotransmitter N -acetylaspartylglutamate (NAAG) to N -acetylaspartate (NAA) and glutamate [ 9 ], and multiple independent research groups have demonstrated the therapeutic benefit of inhibiting GCPII to treat neurological dysfunctions [ 6 , 7 , 8 ]. Similarly, perturbation in GCPII expression has been reported in cancer neovasculature [ 10 ], tumor angiogenesis [ 11 ], as well as in inflammatory bowel disease [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%